APPLICATION OF LINGUISTIC, COMMUNICATIVE AND PRAGMATIC COMPETENCES FOR FOREIGN LANGUAGE TEACHING - Kattaboeva Dilrabo Kattaboevna (Western European Studies, 2023)
The article discusses the development of the content of the concept of "competence" in the history of linguistics, as well as the methodology of teaching languages, analyzes the main concepts of scientists and presents the structures of linguistic competence by different authors. Based on the analysis, the definition of linguistic, pragmatic and communicative competences and the main stages of the formation of linguistic competencies in the process of teaching a foreign language are studied
Keywords: linguistic competence; pragmatic competence; language teaching competence